STUDI MAKNA TARIAN TRADISIONAL KAKAVU - Aprianti, Irdha (Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Tadulako, 2018)
The purpose of this study was to find out the form of nonverbal Kakavu traditional dance in Dalaka Village, Donggala Regency, Central Sulawesi and to find out the meaning of Kakavu traditional dance in Dalaka, Donggala Regency, Central Sulawesi. This type of research is conducted in a qualitative descriptive manner. Data collection techniques are carried out by observation and in-depth interviews. Informants in this study amounted to 5 (people) with the consideration that the appointed informants were representatives who could provide accurate information in accordance with the needs and objects of research. The results of this study indicate that the Kakavu dance is a dance that tells about the lives of the people of Dalaka Village, whose majority of the population works as makers of mattresses and pillows. This Kakavu dance was formed to explain the process of beginning to the end of making mattresses and pillows in Dalaka Village. There are forms of non-verbal messages, arifaktual, and kinesik meanings. These forms of non-verbal and arifaktual messages have certain meanings for the indigenous Kaili tribe in Dalaka Village. Kinesik's meaning in the Kakavu dance is in the form of facial expressions expressed from the dancers 'faces, the eye contact that occurs in the Kakavu dance has the meaning of the message, and then the dancers' body movements in the Kakavu dance have eleven movements namely moseka, moboba, motala, mokambi, menggoliaka, modude, mosore, mokosini, moaso, modau, and mobauu. But in the eleventh movement there are two movements that form the core of the Kakavu Dance which have important meanings, namely; moseka movement (peeling kapok from the skin). In this movement, they want to convey that how hard and hardworking the people of Dalaka Village are. Besides moseka, the modau movement (sewing the edge of the mattress). In this movement, they want to convey that the Dalaka Village community has so much hope in the progress of their village and they have a strong determination to achieve that expectation.